PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pratama, Leo Nardo; Setiawan, Marwan (JUMANJI (JURNAL MANAJEMEN JAMBI), 2023)
This research aims to analyze the influence of financial performance on stock prices using the Return On Assets (ROA) and Return On Equity (ROE) variables. The results of the research show that the Return On Asset (ROA) variable has a significant effect on the share prices of agricultural sector companies, and Return On Equity (ROE) has a significant effect on the share prices of the agricultural sector.